ISOLATION AND CHARACTERIZATION OF ANTIOXIDANT (FLAVONE-3-RUTINOSIDE, 3, 3’, 4’, 5, 7-PENTAHYDROXY) FROM LEAVES OF MELIA DUBIA - G, DAYANA JEYALEELA; N, BALASUBRAMANI; VIMALA J, DR. ROSALINE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Various antioxidants are extensively found at different levels in many medicinal plants. This study mainly focuses on identification and separation of antioxidant from the leaf extract of Melia dubia. Materials and Methods: Soxhlet extraction adopted for extraction using solvents, namely hexane, chloroform, ethyl acetate, 70% Ethanol, methanol, and water. The antioxidant capacity of six extracts was analyzed by quick and convenient 1, 1-diphenyl-2-picrylhydrazyl method. The compound responsible for high scavenging activity was isolated and separated by chromatography techniques such as thin-layer chromatography and high-performance liquid chromatography. Antioxidant was characterized by UV-visible, Fourier-transform infrared (FT-IR), H1-nuclear magnetic resonance (NMR), C13-NMR, and mass spectroscopy. Results and Discussion: On extraction, water extract shows the highest yield percentage followed by methanol and 70% ethanol. Based on our results, IC50 value among the extracts, methanol and 70% ethanol, showed high antioxidant activity. Antioxidant which is commonly present in the methanol and 70% ethanol extract is flavone-3-rutinoside, 3, 3’, 4’, 5, 7-pentahydroxy. Conclusion: The occurrence of the antioxidant, i.e. rutin flavonoid was identified in the study, and the biological activity of this compound will determine in future work.